An evaluation of the book and periodical collections of the library of the Loyola School of Theology Ateneo de Manila University - Tan, Felipe Jr.; Vallejo, Rosa M.; Cruz, Ma. Divina P. (Quezon City Institute of Library Science, University of the Philippines Diliman, 1988)
This research work aims to evaluate the book and periodical collections of the Loyola School of Theology Library. Three procedures were used to accomplish this purpose. These are quantitative analysis, qualitative analysis and citation analysis. For quantitative and citation analyses, the statistical method was used for data gathering, and for qualitative analysis, the checklisting and impressionistic methods were utilized. These methods were applied during the first semester of the school year 1987-1988.
The book collection of the Loyola Library, at the time this research was conducted, was at 37,270 titles, equivalent to 57,305 volumes. The periodical collection consists of 13,947 bound volumes. Overall, the Loyola Library has 71,252 volumes in its book and periodical collections.
The Loyola Library uses the Library of Congress classification scheme. Of the 37,270 titles, 28,370 (76.12 per cent) belong to class B (Philosophy and Religion). On the other hand, the periodical collection has 577 titles (90.30 percent) classified under class B. The book and periodical collections of the Loyola Library is, therefore, strongly theological in nature.
This study concludes that the book and periodical collections of the Loyola Library is very capable in meeting the needs of the faculty and student clientele. Likewise, it is adequate in meeting the needs of the curriculum, as well as the objectives of the Loyola School of Theology. Furthermore, the library collection is capable in meeting the needs of the students in writing theses and dissertations.
The library is strong, quantitatively speaking, in the areas of Roman Catholic studies, doctrinal theology and biblical studies. It is weak in the areas of ethics, Islamic studies and Buddhism. Moreover, the quality of the collection is quite strong in meeting the needs of the curriculum in Roman Catholic studies and methods courses "Th 283: Giving Retreats" and "Th 283.1: Audiovisuals for Evangelization".
The employment of several methods of evaluation demonstrates the adequacy and the high quality of the book and periodical collections of the Loyola Library. Likewise, it pinpointed few weak areas which could be strengthened through collection development.
This study recommends that the library should maintain and, if possible, increase the momentum of its collection development. At the same time, it should strengthen the collection in areas where it is weak. It also recommends that the library should study the possibility of completing the gaps of the periodical collection in selected subject areas in microfiche form. The library should likewise spearhead the establishment of a network of information on theses and dissertations with other theological institutions. Finally, it recommends that the Loyola Library be evaluated every five years to help the library administration in its program of collection development.
This research work aims to evaluate the book and periodical collections of the Loyola School of Theology Library. Three procedures were used to accomplish this purpose. These are quantitative analysis, qualitative analysis and citation analysis. For quantitative and citation analyses, the statistical method was used for data gathering, and for qualitative analysis, the checklisting and impressionistic methods were utilized. These methods were applied during the first semester of the school year 1987-1988.
Typescript.
Vita.
Special Problem (Master of Library Science)
Keywords: Acquisitions (Libraries) -- Evaluation; Ateneo de Manila University (Quezon City) Loyola School of Theology Library